FOODSAFETYKNOWLEDGE,ATTITUDESANDPRACTICESAMONG RESTAURANTS’ FOODHANDLERS IN NORTH LEBANON: EVALUATION OF THE FOOD SAFETY TRAINING - Jana, Halabi; Hanan, Hijazi; Khaled, El Omari; Imad, Al Kassaa; Mazen, Zaylaa (university of eloued -جامعة الوادي, 2022)
This study was conducted to assess food safety knowledge, attitudes and practices among restaurant food handlers in North Lebanon and to determine what impact the food safety intervention had on the performance of workers.A structured questionnaire of 35 questions has been used to collect information on socio-demographic characteristics, knowledge, attitudes and practices for 110 food handlersrandomly working in 38 food service establishments via face-to-face questioning interviews during three months.The intervention was made to a subgroup of 13 participants followed by a reassessment. The average percentage scores of all food handlers for knowledge, attitudes, andpractices were 63.78%, 83.63% and 81%, respectively.For the 13 participants who received theintervention, a significant improvement was observed in their performance after the training (p˂0.001)
ARTICLE
Keywords: Food safety; foodbornediseases; food handlers; KAP;Lebanon